A NEW SPECIES OF PANDANUS (PANDANACEAE) FROM BINTUNI BAY, WEST PAPUA - Harry Wiriadinata (REINWARDTIA, 2009)
WIRIADINATA, H. 2009. A new species of Pandanus (Pandanaceae) from Bintuni Bay, West Papua. Reinwardtia 12(5): 443–446. — Pandanus bintuniensis Wiriadinata collected from Bintuni Bay, West Papua is described. It is very close to P. permicron Kanehira, but differs in wider leaf and brownish green coloured young leaf.